The effects of exercise on function and pain following total hip arthroplasty: a systematic literature review and meta-analysis. (25th November 2022) - Tang, Wilson; Flavell, Carol Ann; Grant, Andrea; Doma, Kenji
Abstract: Background: Previous reviews have reported the efficacy of exercise interventions following total hip arthroplasty (THA), but poor inter-study comparability of low-quality studies, and outcome measure heterogeneity predominate. Conclusions regarding exercise intervention efficacy following THA are lacking. Objectives: Conduct a systematic literature review with meta-analysis to report the effects of exercise following THA, using self-reported outcome measures of function and pain, and clinical tests for gait capacity. Methods: An electronic database search of CINAHL, Informit, Medline, Physiotherapy Evidence Database, Scopus, and SportDiscus was conducted. Included studies (1) reported exercise interventions in adult populations following THA; (2) reported outcomes either of physical function, pain intensity, or clinical gait capacity; (3) were randomised controlled trials published in English. Study appraisal was conducted using PEDro scale. A meta-analysis was conducted to report intervention effect size and statistical significance between experimental and control groups. Results: Searches yielded 5, 997 studies. Twenty-four studies underwent systematic review. Twelve were eligible for meta-analysis. Study quality ranged from fair to excellent (median = 7, range = 5–9/10). Exercise interventions included hydrotherapy, and progressive resistance, gait, task-based, upper-limb, and sports therapy training. Significant between-group differences in self-reported function, pain, and gait velocity were observed at short-term follow-up, favouring exercise intervention groups. At long-term follow-up, these improvements were not significant. Conclusions: This review identified that exercise interventions significantly improved self-reported physical function, pain intensity and gait velocity following THA in the short term. Further research is required to clarify long-term exercise effects, and the most effective exercise intervention, in studies which detail the interventions explicitly.